Novel architecture of onem2m-based convergence platform for mixed reality and iot - Lee, Seungwoon; Kil, Woogeun; Roh, Byeong Hee; Kim, S. J.; Kang, Jin Suk (Computers, Materials and Continua, 2022)
There have been numerous works proposed to merge augmented reality/mixed reality (AR/MR) and Internet of Things (IoT) in various ways. However, they have focused on their specific target applications and have limitations on interoperability or reusability when utilizing them to different domains or adding other devices to the system. This paper proposes a novel architecture of a convergence platform for AR/MR and IoT systems and services. The proposed architecture adopts the oneM2M IoT standard as the basic framework that converges AR/MR and IoT systems and enables the development of application services used in general-purpose environments without being subordinate to specific systems, domains, and device manufacturers. We implement the proposed architecture utilizing the open-source oneM2M-based IoT server and device platforms released by the open alliance for IoT standards (OCEAN) and Microsoft HoloLens as an MR device platform. We also suggest and demonstrate the practical use cases and discuss the advantages of the proposed architecture.
Keywords: Augmented realty; Convergence platform; Internet of thing; MicroSoft; Microsoft hololens; Mixed reality; Novel architecture; Onem2m; Proposed architectures; Augmented realty (AR); Convergence platform; Internet of things (IoT); Microsoft HoloLens; Mixed reality (MR); OneM2M